Study on Harmonic Suppression Method of Permanent Magnet Synchronous Motor in High Voltage Wire Inspection Robot - Ma Long; Xu Xiaoyi; Mao Yanfang; Wang Baocang (Engineering Reports)
ABSTRACT The working environment for safety inspection of high‐voltage wires is very harsh, such as high temperature, low temperature, high altitude, wind, and rain weather, etc. High‐voltage wire inspection robots can replace human work. For the robot, the harmonic suppression of the permanent magnet synchronous motor will determine the completion of inspection work. Therefore, from the point of view of the control algorithm, this paper analyzes the speed, time, and frequency domain signals of the motor driven by the Space Vector Modulation DTC (SVM‐DTC) method. Then, the d‐axis current is equal to zero in the adjustment control algorithm, and a direct torque control method of the permanent magnet synchronous motor space vector modulation based on time‐varying flux amplitude is proposed. This control algorithm can effectively suppress the amplitude of harmonic components while reducing the fluctuation of the rotational speed signal in the time domain. After the improved motor control strategy, the torque fluctuation of the motor decreased by 42.86%. It greatly improves the stability of the robot in the operation of high‐voltage electric wire. Finally, the effectiveness of this method is verified by experiments.